Association between plasma leptin/adiponectin ratios with the extent and severity of coronary artery disease - Rahmani, Asghar (BMC Cardiovasc Disord, 2020)
BACKGROUND: Leptin can have a direct effect on endothelial and vascular smooth muscle cells and high level of leptin is involved in the pathogenesis of atherosclerosis. This study aimed to determine the relationship between leptin/adiponectin (L/A) ratio and the extent and severity of coronary artery disease (CAD). METHODS: This case-control study was conducted in an educational hospital in Ilam, Iran from June 2014 to September 2015. Totally 300 participants including 150 patients with CAD (case group) and 150 healthy individuals (control group) were selected and their plasma leptin, adiponectin and leptin/adiponectin ratio was measured. The extent and severity of coronary artery disease were assayed based on the number of involved vessels and Gensini score (GS) and the relation between scores and L/A findings were compared between cases and controls. RESULTS: Totally, 300 participants including 150 (42.7% male), mean age 59.5 ± 11.4 years as cases and 150 (50.7% male), mean age 59.8 ± 10.7 as controls were analyzed. Plasma level of leptin and L/A ratio were higher in cases compared to controls, but level of adiponectin was significantly lower in CAD patients than the control group. More number of involved coronary vessels was significantly correlated to higher level of plasma leptin, L/A ratio and lower level of adiponectin among case group. Moreover, adiponectin was negatively and leptin or L/A ratio were positively correlated with number of involved vessels. 7.3% of cases had only one involved vessel, 42.7% had two involved vessels, and 50% of total patients had involved vessels and the mean ± SD of GS in the case group was 23.6 ± 6.9. CONCLUSIONS: Plasma levels of leptin, and adiponectin can indicate the extent of coronary artery diseases but leptin may be a better marker of extent of CAD than either L/A ratio or adiponectin separately.